An experimental study of girder-borne sound pressure emission and acceleration - Szyszka, Łukasz (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
The subject of the paper is an experimental study on girder-borne sound pressure emission. The sources of excitation are hammer and modal shaker. The structure researched is simply supported steel plate girder of the size: 7.95 m x 1.5 m. The study covers acceleration and sound pressure level measurements (SPL), and SPL estimation based on the accelerations measured. The correlation factor for higher estimation accuracy in lower frequency bands is proposed.